Improved performance of organic solar cells by incorporating silica-coated silver nanoparticles in the buffer layer. Issue 5 (10th December 2014) - Hao, Yang; Song, Jingcheng; Yang, Fan; Hao, Yuying; Sun, Qinjun; Guo, Junjie; Cui, Yanxia; Wang, Hua; Zhu, Furong
Abstract : An enhancement of 19.2% in PCE is obtained by incorporating silica-coated silver nanoparticles into the buffer layer of organic solar cells. Abstract : It is demonstrated that the use of silica-coated silver nanoparticles (AgNPs) in the buffer layer improves the performance of organic solar cells (OSCs). It is found that only large sized AgNPs are advantageous for increasing the electric field distribution in the active layer, and therefore, increasing light absorption, caused by the localized surface plasmonic resonance and far-field scattering. Furthermore, the scattering of silica-coated AgNPs is more important to the light harvesting because of the existence of the silica coating. It is also demonstrated that the silica coating is favorable for enhancing the exciton dissociation because of the reduction of the exciton quenching that occurred at the interface between the bare AgNPs and the active layer. Furthermore, silica-coated AgNPs also promote hole transport and extraction, which is presumably explained by the introduction of "dopant" levels within the band gap of the poly(3, 4-ethylenedioxythiophene)–poly(styrenesulfonate) and reduction of hole trapping of a bare silver surface. The combination of all these benefits results in a 25.4% improvement in photocurrent density and an increase of 19.2% in power conversion efficiency. This work indicates that using silica-coated AgNPs as light trapping elements is more efficient than using bare AgNPs in plasmonic organic solar cells. The systematic exploration of the optical and electrical effects of silica-coated AgNPs contributes to a more comprehensive understanding of the mechanism of performance improvement of the plasmonic OSCs.